2018
DOI: 10.1103/physrevb.98.085414
|View full text |Cite
|
Sign up to set email alerts
|

Strain-engineered Majorana zero energy modes and φ0 Josephson state in black phosphorus

Abstract: We develop a theory for strain control of Majorana zero energy modes and the Josephson effect in black phosphorus (BP) devices proximity coupled to a superconductor. Employing realistic values for the band parameters subject to strain, we show that the strain closes the intrinsic band gap of BP; however, the proximity effect from the superconductor reopens it and creates Dirac and Weyl nodes. Our results illustrate that Majorana zero energy flat bands connect the nodes within the band-inverted regime in which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 83 publications
5
47
0
Order By: Relevance
“…As recently demonstrated, control of these parameters is possible by, for example, applying strain to the system. [9][10][11] To further shed light on the symmetry profiles of these superconducting correlations, in Figs. 1-3, we present a few representative profiles for the real and imaginary parts of the equal-Pspin and opposite-Pspin components as a function of the momenta k x and k y .…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
See 4 more Smart Citations
“…As recently demonstrated, control of these parameters is possible by, for example, applying strain to the system. [9][10][11] To further shed light on the symmetry profiles of these superconducting correlations, in Figs. 1-3, we present a few representative profiles for the real and imaginary parts of the equal-Pspin and opposite-Pspin components as a function of the momenta k x and k y .…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
“…Such situations can be precisely determined by first-principles calculations; e.g., when the system experiences external strain or is subject to doping and intercalation. A practical example is when a black phosphorus mono- layer is under the application of an external strain, as was recently discussed [9][10][11] . The band-structure parameters were obtained using density-functional-theory computations, and symmetry calculations demonstrated that the momenta coefficients can change sign depending on the strength and direction of the applied in-plane strain.…”
Section: A Symmetry Profile Of Superconducting Pair Correlationsmentioning
confidence: 99%
See 3 more Smart Citations